Association of serum and local GRP78 and CHOP expressions with disease progression in patients with non-traumatic osteonecrosis of femoral head - Peng Zhang; Qing-He Ye; Wen-Xiu Zhu; Yong-Heng Zhao; Hong-Xun Zhu; Biao-Fang Wei (Journal of Orthopaedic Surgery and Research)
Abstract Background The endoplasmic reticulum stress (ER stress) has been involved in various musculoskeletal disorders including non-traumatic osteonecrosis of femoral head (NT-ONFH). Objective The current study aimed to investigate the association of glucose-regulated protein 78 (GRP78) as well as CCAAT/enhancer-binding protein homologous protein (CHOP) expressions in serum and femoral head (FH) tissues with NT-ONFH’s severity. Methods We enrolled NT-ONFH patients (n = 150) alongside healthy controls (HCs, n = 150). Meanwhile, 49 patients with femoral neck fracture (FNF) were also enrolled. Serum CHOP and GRP78 levels were determined through enzyme linked immunosorbent assay (ELISA). Local CHOP and GRP78 expressions were detected by immunohistochemistry, western blot, alongside real-time polymerase chain reaction (RT-PCR). Radiographic severity was assessed by FICAT grading system. The visual analogue scale (VAS) together with Harris hip score (HHS) were utilized to determine symptomatic severity. Results Serum CHOP and GRP78 levels were markedly increased in NT-ONFH patients than HCs. NT-ONFH patients at FICAT stage 4 showed significant higher serum CHOP and GRP78 levels in contrast with those at stage 3. Furthermore, patients at stage 3 demonstrated higher serum CHOP and GRP78 levels than those at stage 2. There was a positive correlation observed between the serum CHOP and GRP78 levels and the severity of the FICAT stages. A total of 42 ONFH patients at FICAT stage 3, 40 patients at FICAT stage 4, and 49 FNF patients received total hip replacement (THR). The mRNA and protein levels of CHOP and GRP78 were elevated in necrotic area compared to the non-necrotic area of ONFH patients and the FH tissues of FNF patients with statistical significance. The expression levels of CHOP and GRP78 within the local tissues were significantly elevated in patients at FICAT stage 4 as opposed to those at stage 3. Besides, ROC curve analysis indicated that serum and local CHOP and GRP78 expressions may act as indicators of disease progression. The levels of CHOP and GRP78, both in serum and at the local site, were in a positive correlation with VAS scores but an inverse relationship with HHS. Conclusions Serum and local GRP78 as well as CHOP expressions were positively linked with disease progression in NT-ONFH patients. Potential therapeutics targeting ER stress related protein may serve as a method for alleviating NT-ONFH.